Visita de la ciudad de dresde de la mano del poeta Jaime Siles y de un cicerón circunstanciado: A.D.A. (“Te invito hoy a un viaje”) - Díaz Arenas, Ángel (Acta Hispanica, 2016)
The present work pays homage to Jaime Siles and evokes several moments of the friendship that the author of this essay has with the recognized contemporary Spanish poet. He summarizes and briefly comments on the poetic volumes of Jaime Siles and pays particular attention to his latest poetry book Extra Hours which includes the poem that treats the German city, Dresden.